Z badań nad homeryzmami "Potopu" Henryka Sienkiewicza - Macjon, Józef (Collectanea Philologica, 1995)
In reference to a comparative study of Sienkiewicz' s historical trilogy three episodes in The Deluge bear striking resemblance to those in Odyssey (translated by Lucjan Siemieński) - the fact that seems to have escaped to critics' notice. The story of Kmicic's bow, especially a description of the archer's action just about to shoot an arrow, together with an accompanying simile (The Deluge, vol. 3, chap. XII) is patterned on a motif of Odysseus' bow (Odyssey, XXI, 11-33; 409-411). The episode in which Kuklinowski takes revenge on Kmicic, and then that of Kmicic's revenge on Kuklinowski (The Deluge vol. 3, chap. XVIll) shows the writer's familiarity with the scene of Melanthios - the Goatherd's capture (Odyssey, XXII, 173-205). In the chase after Babinicz, The General Douglas comes across a bunch of Swedish soldiers hanged by some Polish peasants (The Deluge, vol. 6, chap. IX). The story of the event is an excelent example of the use of Homeric simile (Odyssey, XXII, 481–487).